Prvi koraki do seznama temeljnega šolskega besedišča - Kosem, Iztok (Sodobna pedagogika, 2025)
In this paper, we address the issue of creating a list of basic school vocabulary for the Slovene language that would be comparable to similar word lists we know for English and other languages. Such word lists not only serve to improve teaching materials and language tools for Slovene, but can also contribute to the upgrading of teaching materials for other subjects and to the development of teaching standards. In the introductory section, we first provide an overview of existing word lists for foreign languages, and then present the relevant existing word lists for Slovene, focusing on a reference list of general vocabulary and two lists of textbook vocabulary. This is followed by a detailed presentation of relevant current corpus resources for Slovene in the school environment. We then conduct an analysis of the existing Slovene vocabulary lists, comparing them with each other and with word lists from relevant corpora, examining consistencies and differences in coverage of key lexical units. It turns out that each list has certain shortcomings and that the difference between reception and production has to be taken into account. We also perform a diachronic analysis of a selected sample of words from the corpora of textbooks and school written products, which reveals changes in word usage not only at the temporal level but also at the semantic level. In conclusion, we summarise the main findings of the study and highlight suggestions for further research that could contribute to the production of a comprehensive and functional list of basic school vocabulary for the Slovene language.
Keywords: corpus of textbooks; corpus Šolar; korpus Šolar; korpus Učbeniki; language use in schools; raba jezika v šoli; seznami besed; word lists